Kritik Sanad dan Matan Hadis dalam Shahih Muslim yang Dianggap Lemah Nasiruddin al-Albani - Beko Hendro (IAIN Syekh Nurjati Cirebon, 2021)
This article discusseses the hadith on reading/memorizing the first ten verses of surah al-Kahfi in Saheeh Muslim which is considered dhaif by Nasiruddin al-Albani. Al-Albani did not explicitly mention the reason for the hadith. This research uses the methodology of criticism of isd and matan –naq ad-dakhili wa naq al-khariji-. In this study the authors found one of the informants from the sanad line that the Muslim Imam indicated was weak. It is Mu'az ibn Hisya'm who is judged by Ibn Mu'in. Predicate suduq one level below tsiqah.However, the quality of the narrator who suduq does not weaken the hadith, but it is hasan by considering other lines of transmission.